Outcome of Occupational Asthma after Removal from Exposure: A Follow-Up Study. Issue 2 (2010) - Lemiere, Catherine; Chaboillez, Simone; Welman, Mélanie; Maghni, Karim
Abstract : BACKGROUND: Despite being removed from their workplace, the majority of workers with occupational asthma (OA) remain afflicted with asthma. OBJECTIVES: To assess the time course of clinical, functional and inflammatory parameters in subjects with OA over a four-year period, and whether the airway inflammation observed at the time of the diagnosis predicts the outcome of OA. METHODS: The present study was a four-year, prospective, longitudinal investigation of workers with OA. Spirometry, methacholine challenge and sputum induction were performed at two weeks, and followed up at six months, and one, two, three and four years after the performance of specific inhalation challenges. RESULTS: A total of 24 subjects were enrolled. Overall, clinical and functional characteristics remained stable during the four-year follow-up period. Sputum eosinophil (Eos) counts decreased within two weeks after exposure. Two groups of subjects were identified according to low (less than 2%, Eos−) or high (2% or greater, Eos+) Eos counts after exposure to the offending agent. The Eos+ group decreased their dose of inhaled corticosteroids, had a trend toward an improvement of airway responsiveness as well as a stable forced expiratory volume in 1 s (FEV1 ), whereas the Eos− group showed a decrease in FEV1, without any improvement in their functional parameters. The Eos− group also had an increase in sputum neutrophils after exposure to the occupational agents as well as during the follow-up period. CONCLUSION: There was a rapid decrease in eosinophilic inflammation after removal from exposure. Subjects with a noneosinophilic asthmatic reaction during specific inhalation challenge seemed to have a poorer prognosis than subjects with eosinophilic airway inflammation.